How to Make Shredded for Family Consumption and Opportunities to Increase Family Income for Mothers Rt 06 Rw 09 at Palmerah - Zulkarnain Arif; Maryani Maryani; Sarim Sarim (Social Economics and Ecology International Journal (SEEIJ), 2021)
Fish is one of the food sources of animal protein (fish) which is widely liked and consumed by the public. This is aside from being relatively inexpensive and easy to obtain, as well as a high nutritional value that can maintain stability and health and can also improve brain intelligence in children. Shredded is one of the traditional processed food products that have long been known by the community. In general, shredded meat is made from beef and other animal meat. Shredded fish contains high enough nutritional components that are needed by our body. To build a culture that is cultured, spiritual, intellectual and intelligent, Palmerah Sub-district, West Jakarta has created thematic villages in six villages in its area. Palmerah Sub-district is a sub-district with a dense population. To support the smart village launched by Mr. Firman as the Head of Palmerah District. Where is a clean and healthy lifestyle and makes the village smart, by inviting families, especially children, to eat fish. One of the processing is by processing fish into shredded fish. Housewives and young people who have not worked are expected to make business opportunities to increase income and can also be consumed by families themselves. Training from the initial stage to completion requires eight months divided into several stages starting from needs analysis, introduction of fish and equipment and the manufacturing process, as well as packaging and the final stage is that the product can be sold through markets, stalls or through online media.